Investigations of functional composition "Effect" for special foods (for overweight people) - Притульська, Наталія Володимирівна; Вдовенко, Наталія Володимирівна; Лошкарьова, Євгенія Олександрівна; Сєногонова, Галина Ігорівна (Technology audit and production reserves, 2015)
This paper presents an analysis of development results of functional composition "Effect", which is balanced in the ratio of basic components, is well combined with all components of basic recipes, does not impair organoleptic, physical and chemical quality of the new food. It is established an impact effectiveness of the functional composition on the functional state of the body, improving the metabolism in the body, blocking the synthesis of fat in adipose tissue, decreasing the absorption of carbohydrates and fats in the digestive tract and removing excess fluid, accelerating the adipolysis of fat molecules and transformation of fat in the free energy, increasing its expenditure. It is confirmed a social and economic impact of the implementation of developments, which is to expand the range of sweets with certain functional actions for overweight people, which will accelerate the progress of metabolism process, rapid adipolysis (abdominal) in Ukraine, creating an effective alternative to imported sweets.